'Big boys don't cry': Examining the indirect pathway of masculinity discrepancy stress and muscle dysmorphia symptomatology through dimensions of emotion dysregulation. (September 2020) - Cunningham, Mitchell L.; Rodgers, Rachel F.; Lavender, Jason M.; Nagata, Jason M.; Frederick, David; Szabo, Marianna; Murray, Stuart B.
Highlights: Masculinity discrepancy stress was strongly associated with muscle dysmorphia (MD) symptoms. Emotion dysregulation represents an indirect pathway linking these constructs. A unique indirect pathway was lack of access to adaptive emotion regulation strategies. Abstract: Prevailing conceptualizations of muscle dysmorphia (MD) have highlighted the role of adherence to stereotypical ideals of masculinity. In addition, the endorsement of masculine norms has been associated with dysfunctional emotional regulation, itself a correlate of body image psychopathology. Building on this, the present study sought to investigate the indirect relationship between masculinity discrepancy stress (i.e., distress related to one's perceived discrepancy in masculinity) and MD symptomatology via different facets of emotion dysregulation among adult men. A sample of 391 university and community men aged 18–50 years completed an online survey measuring the aforementioned constructs. A test of parallel indirect pathways revealed that emotion dysregulation, as a unitary construct, accounted for a substantial proportion (29.3 %) of the total association between masculinity discrepancy stress and MD symptomatology. Further, a significant unique indirect pathway was found through the specific emotion dysregulation facet of lack of access to adaptive emotion regulation strategies. Together, these findings suggest that emotion dysregulation is a particularly important construct to consider in understanding the relationship between perceived discrepancies in masculinity and MD symptomatology.